Management of the circulation on the intensive care unit. Issue 10 (October 2021) - McIntosh, David; Hutchinson, Dominic
Abstract: The management of the circulation in critically ill patients presents significant challenges. Shock is a potentially reversible life-threatening physiological state characterized by end-organ dysfunction due to an imbalance in oxygen delivery (DO2 ) and tissue demand (VO2 ). Independent of its aetiology, untreated shock precipitates a cascade of pro-inflammatory mediators resulting in cellular damage and end-organ dysfunction. Thus it is the duty of all clinicians to promptly recognize, diagnose and initiate treatments to halt this process. Despite optimum management, shock can progress to multi-organ failure necessitating critical care admission and advanced haemodynamic management. This article will classify shock syndromes, discuss the principles of diagnosis, use of haemodynamic monitoring and management strategies for circulatory failure in the critically ill patient.